Balancing Individual Rights and State Authority in Criminal Justice Reform: A Comparative Analysis of Procedural Fairness and Legal Accountability - Rengga Kusuma Putra; Retno Saraswati; Edvardas Juchnevicius; Aulia Rahman (International Forum of Researchers and Lecturers, 2025)
Background: Criminal justice reform has become a crucial global issue in maintaining the balance between the protection of individual rights and state authority, particularly amid the increasing complexity of law enforcement and the risk of abuse of power. Objective: This study aims to analyze the relationship between the principles of due process of law, legal accountability, and the rule of law within criminal justice systems, as well as to compare their implementation in common law and civil law systems. Methods: This research employs a normative and comparative approach through the analysis of legal regulations, criminal justice practices, case studies of procedural violations, and cross-country comparisons, supported by interviews with academics and legal practitioners. Results: The findings indicate that although the principles of due process, legal accountability, and the rule of law are widely recognized, their implementation still faces significant challenges, including weak oversight, procedural inconsistencies, and limited institutional capacity. The comparative analysis also reveals a growing convergence between common law and civil law systems in adopting human rights-based standards, despite differences in procedural approaches. This study concludes that the holistic integration of these three principles is essential to establish a fair, transparent, and accountable criminal justice system.